Seasonal variation of physico-chemical parameters in upstreamrivers of Timah Tasoh Lake, Perlis / Siti Aesah Abdullah - Abdullah, Siti Aesah (2016)
Increasing anthropogenic activities have led to increase heavy metal contamination level in upstream rivers of Timah Tasoh Lake, Perlis. At present, very few studies were reported on the level of heavy metals contamination in this area. Therefore, a study on seasonal variation of physico-chemical parameters was conducted to investigate the effect of season on the level and distribution pattern of these heavy metals. The surface water sample was taken at eleven sampling stations which cover three main regions which are Padang Besar, Wang Kelian and Timah Tasoh in North of Perlis. Samples were analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for heavy metals such as Lead (Pb), Copper (Cu), Zinc (Zn), Lithium (Li), Chromium (Cr), Cadmium (Cd), Nickel (Ni), Cobalt (Co), Arsenic (As), Aluminium (Al) and Manganese (Mn). Overall, the water from all sampling stations was within the acceptable limit except for Cd (>1 ppb), Al (>56 ppb), Mn (>100 ppb) in the dry and the wet season which have recorded elevated concentration above the Interim National Water Quality Standard (INWQS) limit set by the Department of Environmental (DOE) Malaysia. The thematic map generated by integrating Geographical Information System (GIS) with heavy metals data has illustrated the distribution pattern of these metals during seasonal changes. The dataset of physicochemical obtained were subjected to Principal Component Analysis (PCA) and Multiple Linear Regression (MLR). PCA score plot showed that the heavy metals spread homogeneously indicating no differences in their distribution in both seasons. The presence of heavy metals in upstream rivers has high potential to increase heavy metal loading to the Timah Tasoh Lake. MLR analysis was produced model equations in predicting the influence of heavy metals in surface water towards Dissolved Oxygen (DO), Total Dissolved Solid (TDS), Salinity (S) and Electrical Conductivity (EC) as water quality parameters. The coefficient determination (R2) value was in the range of 0.75-0.81 (dry season) 0.75-0.88 (wet season) suggesting that concentration of the heavy metals are correlated to the changed of water quality parameters. The results demonstrated that the application of multivariate and GIS mapping techniques were successfully elaborate the level of heavy metals contamination in upstream rivers of the Timah Tasoh Lake, Perlis.